Repurposing of fluoxetine for antibacterial activities in catheter-associated urinary tract biofilm infections: an in vitro analysis - Muhammad Musthafa Poyil; Rameesha Shafqat; Mamoun A. Alfaki (Universa Medicina, 2023)
BackgroundUrinary tract infections are often initiated by indwelling catheters and bring about serious consequences, especially when they are caused by multidrug-resistant bacterial pathogens. The biofilms of uropathogens such as Enterococcus faecalis and Escherichia coli pose serious challenges. Therefore the scientific world is trying to experiment with alternative drugs to replace conventional antibiotics as the latter are more prone to cause the development of antibacterial resistance. Here, we evaluate the repurposing of the antidepressant fluoxetine as an antibacterial agent against the mentioned pathogens. MethodsTo repurpose fluoxetine for its antibacterial activity against Enterococcus faecalis and Escherichia coli, the agar diffusion method was used. The minimal inhibitory concentration was found by the microdilution method. The drug was also analyzed as a coating on catheters to evaluate its efficiency against biofilm formation by pathogens. Results The drug fluoxetine showed potential antibacterial and anti-biofilm activities. Its minimum inhibitory concentration was found to be 18.75 µg/mL and 37.5 µg/mL against Enterococcus faecalis and Escherichia coli respectively. The antibiofilm activity on polystyrene surfaces was also remarkable as it reduced the formation of Enterococcus faecalis and Escherichia coli biofilms by 70% and 74%, after being treated with 1x MICs and 2x MICs respectively. Conclusions Fluoxetine - one of the drugs of choice in treating depression, when repurposed, has shown considerable antibacterial and antibiofilm effects against two of the major catheter-associated urinary tract infection-causing bacteria - viz. Enterococcus faecalis and Escherichia coli. Therefore, further studies are needed to understand its applicability as an antibacterial agent.